Florida Woods Cockroach Eurycotis floridana (Walker) - Christopher S. Bibbs; Rebecca W. Baldwin (EDIS)
This “peridomestic” organism can be found in structures near the home, such as storage areas, greenhouses, or shelter boxes for other structures such as water pumps. It is one of the species commonly referred to as palmetto bugs and is also called a “stinkroach” or “skunk cockroach” due to its aromatic defensive secretions. This 6-page fact sheet was written by Christopher S. Bibbs and Rebecca W. Baldwin, and published by the UF Department of Entomology and Nematology, December 2011.